STRATEGI KOMUNIKASI PEMANFAATAN DIGITAL MARKETING AGRIBISNIS KOPI DALAM MENINGKATKAN PENDAPATAN PETANI - Prabawa, Tegar (Dharma Duta, 2023)
The COVID-19 pandemic has made it difficult for farmers to market their coffee production, because human mobility is limited. So farmers are forced to switch from conventional marketing processes to digital-based marketing. In addition to the COVID-19 pandemic, increasingly rapid technological developments also affect changes in the marketing system carried out by farmers. So it is hoped that with a digital marketing-based coffee marketing system in increasing farmers' income. Digital marketing also allows coffee marketing to change its form from conventional marketing to digital-based marketing. Digital marketing for coffee is interesting to study because it can be an innovative marketing strategy to be able to survive and realize the 5.0 generation digital revolution. Digital marketing activities that can be carried out in an effort to increase farmers' income are by conducting Publications or Publicity, Events or exhibitions, News or news, Community Involvement (Building Community), Lobbying, Social Investment and conducting communication strategies using a SWOT Analysis of Strengths that owned by coffee farmers are: quality coffee; an affordable price; trained and experienced farmers; partner with coffee companies; and has a large area. Weaknesses that they have are: farmers are still technologically stumped so it is difficult to develop; sales depend on distributors; limited types of coffee; and seasonal crops. Opportunities that can be utilized by coffee farmers are market potentials that are still open. Meanwhile, the threats faced are: a decrease in sales due to low community mobility; intense competition; and land use change.